Respuesta :
Step 1: Simplify both sides of the equation.
[tex]\frac{3}{10}[/tex] (x+2) = 12
([tex]\frac{3}{10}[/tex]) (x) + ([tex]\frac{3}{10}[/tex]) (2) = 12 (Distribute)
[tex]\frac{3}{10}[/tex]x + [tex]\frac{3}{5}[/tex] = 12
Step 2: Subtract 3/5 from both sides.
[tex]\frac{3}{10}[/tex]x + [tex]\frac{3}{5}[/tex] − [tex]\frac{3}{5}[/tex] = 12 − [tex]\frac{3}{5}[/tex]
3/10x=57/5
Step 3: Multiply both sides by [tex]\frac{10}{3}[/tex].
([tex]\frac{10}{3}[/tex]) * ([tex]\frac{3}{10}[/tex]x) = ([tex]\frac{10}{3}[/tex]) * ([tex]\frac{57}{5}[/tex])
Answer:
x = 38
If you need more help comment below.